PERFORMANCE ASSESSMENT DECISION SUPPORT SYSTEM FOR MEDICOM'S BEST EMPLOYEE DETERMINATION WITH FUZZY SUGENO METHOD - Jontinus Manullang; Sartika Dewi Purba (INFOKUM, 2021)
Performance appraisal is important for every employee and useful for the company to determine the next policy action, At Medicom performance appraisal is used to process promotions, performance evaluations, and determining employee achievements, while the variables used are technical ability, conceptual ability and interpersonal relations, with application fuzzy logic in spk with the Sugeno method will make it easier for foundations to determine the best employees, the results show this decision support system can help foundations get decent employees to be the best employees